Ecophysiology in introduced Impatiens species - Ugoletti, Paola (Trinity College (Dublin, Ireland). Department of Botany, 2011)
This thesis aims to improve knowledge of invasion processes through investigation of the invasive strategies of congeneric Impatiens species that vary in invasive status in Ireland. Since a range of physiological traits promote plant fitness, many studies have attempted to compare these traits among invasive and non-invasive species. Meta-analysis and desk-based reviews offer the advantage of highlighting which traits are consistently associated with plant invasiveness. However, comparisons among studies are not straightforward due to the heterogeneity of the approaches used by different authors. In addition, many comparisons have so far chosen unrelated species, a method that is potentially confounded by phylogenetic differences. The most direct approach to identifying the determinants of invasiveness appears to be to make comparisons between related invasive and non-invasive, or less invasive, introduced species.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.